“Los sketch del canal Enchufetv en la plataforma Youtube, y su incidencia en los hábitos de consumo de información en los estudiantes de la carrera de comunicación social de la universidad nacional de Chimborazo, en el periodo junio-diciembre de 2015” - Quishpi Altamirano, Byron Fernando (2016)
The present study pretends to establish the influence of some sketches on a channel called “Enchufetv” on YouTube and their incidence on consuming habits in students of Social Communication at the National University of Chimborazo. In Chapter One, the outline of the problem, its formulation, justification and objectives are described in the context where the investigation will be carried out. Chapter Two is divided into four units that contain the following: Unit 1 is based on communication and culture that according to some authors describe the way how a society developed due to the internet and TICS. Unit 2 entitled: Consume of Information describes the steps that internet users view certain types of contents where it is observed that the use of YouTube serves for entertaining. Unit Three references the major of Social Communication at the National University of Chimborazo, the place where the study was applied. Unit Four called “Enchufetv” is about the production, marketing among other aspects on the channel. Likewise, the incidence of sceneries and the most relevant characters to make the program trendy. Chapter Three is about the analysis and interpretation of results obtained from a survey. At the same time, the interviews conducted to several educators who provided their opinion to understand the problem. Chapter Four presents the conclusions and recommendations that let people know the sociocultural impact of the study.